Women's Identity Construction and Identity from the Perspective of Gender Theory: Examination of Gender Discourse based on the Film Barbie - Zheng, Shuhua (Transactions on Social Science, Education and Humanities Research, 2024)
The Barbie film directed by Greta Govig became a new milestone in feminist cinema when it set a box office record in 2023. The film not only presents the portrayal of women in a patriarchal society, but also critiques gender stereotypes with humour, triggering a global feminist discussion. This paper focuses on the construction of women's identity and the representation of women's identity in the film Barbie from the perspective of gender theory and in four parts. The first part is the introductory section, mainly covering the research background and significance of this paper; The second part explores the female identity construction of Barbie from the aspects of appearance and social image; The third part explores the female identity of Barbie from the perspectives of male and female; The fourth part mainly combines and summarizes the previous content, and at the same time, combines social scholars' and film critics' interpretations of the film to deepen readers' understanding of the modern portrayal of women on screen.